2021
DOI: 10.1002/fsn3.2664
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid‐enriched extract from Millettia speciosa Champ prevents obesity by regulating thermogenesis and lipid metabolism in high‐fat diet–induced obese C57BL/6 mice

Abstract: Millettia speciosa (M. speciosa) Champ is a medicinal and edible plant. The roots are rich in flavonoids, which possess multiple biological activities, including lipid‐lowering effects. This study aimed to explore the effect of flavonoid‐enriched extract from M. speciosa (FMS) on obesity. The UPLC‐Q‐TOF‐MS analysis and chromatographic analysis were adopted to identify flavonoid compounds in FMS. Male C57BL/6J mice were fed with a high‐fat diet for 3 months and were then treated with FMS (50 or 100 mg/kg/d) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…A crude extract of NP demonstrated antiobesity effects in a mouse model fed a high-fat diet. Another study also showed that flavonoids extracted from N. speciosa, similar to polysaccharides, help prevent obesity by regulating thermogenesis and lipid metabolism in mice (Wang et al 2022a). NP restored the balance of gut microbiota, becoming a promising prebiotic for managing obesity (Li et al 2022).…”
Section: Introductionmentioning
confidence: 96%
“…A crude extract of NP demonstrated antiobesity effects in a mouse model fed a high-fat diet. Another study also showed that flavonoids extracted from N. speciosa, similar to polysaccharides, help prevent obesity by regulating thermogenesis and lipid metabolism in mice (Wang et al 2022a). NP restored the balance of gut microbiota, becoming a promising prebiotic for managing obesity (Li et al 2022).…”
Section: Introductionmentioning
confidence: 96%
“…Numerous experimental and epidemiological research have proven that taking foods abundant in polyphenols and dietary supplements can effectively decrease the risk of developing CVD (Scalbert et al., 2005 ). Clinical trials and animal studies suggested that polyphenols could modify glucose and lipid metabolism (Matacchione et al., 2020 ; Ramos et al., 2023 ; Wang, Ma, et al., 2022 ). Berries are well‐described as interesting sources of polyphenols, especially anthocyanins (de Souza et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Millettia speciosa ( M. speciosa ) Champ (MSC), alias Niudali—the dry root of Millettia genus of the Leguminosae family—is a healthy food type with medicinal and edible homology, which preferentially grows in tropical and subtropical areas, primarily including the Guangdong, Guangxi and Hainan provinces of China. 1,2 It tastes sweet, has little odour, and shows outstanding capacity for restoring lungs and loins, strengthening tendons, and improving kidney function. 3 According to recorded annals, its medicinal history dates back to the late Ming and early Qing dynasties, when its many virtues were recorded, including tonifying deficient Runfei, stimulating blood circulation, and relaxing muscles and joints.…”
mentioning
confidence: 99%